Directions to Preparing Multiple Choice Items in General English Language Tests of Universities - H. Sharifi (Babol University of Medical Sciences, 2010)
Testing is one of the most important parts of teaching and presenting learning techniques to university students in all languages especially English language that is used for measuring learners’ capabilities and academic progress. This article is dealing with multiple-choice items tests that are the best type of objective test used for preventing tedium and guess in answering and also easiness in correcting the answer sheets. Since designing good test or rational distracter items is very difficult and choosing non rational distracter items is an unfavorable and nonstandard act, ability and competence of the language teacher is very essential. Therefore, the quality of multiple–choice items needs the necessity of (why and valuation of what subject) in addition to knowledge, adequate experience in teaching, accuracy and attention focus, faculty and regarding testing rules for the question maker. The problems that English language teachers face are as following: lack of necessary educational periods for preparing multiple choice items questions and not having access to reliable scientific sources in Persian language in order to acquire the necessary information. Directions to preparing multiple choice items in English language test includes explanations about the main points in designing and preparing questions of the four basic skills of language (listening, speaking, reading and writing).